Effects of living at moderate altitude and training at low to moderate altitude on haematoligical characteristics and sea level performance of elite triathletes - Jourdan, A.; Razoilo, J.; Almeida, J.-P.; Alves, F. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Altitude training is a common procedure in endurance sports training carried away with the purpose of increasing blood hemoglobin (Hb) concentration and oxygen-carrying capacity induced by the process of acclimatization to reduced inspiratory partial pressure of oxygen. The aim of this study was to follow-up the alterations in haematological and performance parameters at sea-level in a group of international level triathletes as a result of living at moderate altitude and training at variable altitude (600m to 2300m) on sea level performance. Methods A total of 13 Portuguese national team triahletes participated in this study (age: 20.92±2.53 years). Five integrated a control group for performance evaluation. Seven participated on a first study (S1) where swim performance (2500m freestyle) and haematological variables - haematocrit (HTC), (Hb) and ferritin (Fer) concentrations, red blood cells count (RBC) and percent reticulocytes (Ret) - were evaluated before and after a training camp of 21 days in high moderate altitude (1860 m). Five of the former athletes plus one other athlete participated in a 2nd study (S2) concerning the attendance of another training camp at an altitude of 2100m which evaluation procedures involved the determination at sea level of the swim velocity at a lactate concentration of 4 mmol.l-1 (v4), a timed distance of 1500 m freestyle, a maximal aerobic power test and the determination of HTC, Hb, Fer and RBC. Training sessions were distributed by different altitudes depending on the discipline: swimming at 2100m, running and cycling between 600m and 2300m in S1, and swimming at 2300m, running and cycling between 900m and 2100m in S2. More intensive training sessions were performed at low altitude. A Wilcoxon test was performed between the pre- and post-altitude values of the swimming and cycle ergometer evaluations and significance was set at p<0.05. For haematological variables and timed 1500m freestyle (three testing moments) the same statistical method was used and significance was set at p<0.017 (Bonferroni adjustement in order to prevent Type I error). Discussion/Conclusion Both altitude-training programs increased swimming performance consistently. Submaximal work capacity as revealed by v4 was also improved significantly. VO2max however showed no differences with exposure to hypoxia in spite of individual increases of 3.5% to 16.7%. In S1, Hb showed significant increase as expected, contrarily to S2 where the increment of HTC may express a decrease in plasma volume. The positive haematological changes observed in S1 and uncertain in S2 may be explained by the difference of time spent in low altitude training and the lower altitude used in the former. This study confirms the efficacy of the "living high - training low" model for performance improvement of endurance athletes.